2006
DOI: 10.2225/vol9-issue3-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vitro micropropagation protocol for Mecardonia tenella

Abstract: The Mecardonia genus belongs to the Scrophulariaceae family, composed by 37 species, five of them original of Argentina. M. tenella is an attractive herbaceous native plant characterized by its intensive green foliage and their abundant ring shaped yellow flowers (Zuloaga and Morrone, 1999). It is a very interesting plant for pot and/or garden. A trait to improve in this species is the size of the flowers. To start a breeding program applying biotechnological approaches (plant transformation or in vitro mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…But unlike the latter, the formulations with relatively lower concentrations resulted in poorly developed multiple shoots, which were pale green and lanky in appearance. This may be due to the minimum levels of exogenous PGRs required to balance with endogenous plant hormones for retaining the plant health (Alderete et al 2006), which was not present in the formulations with relatively lower concentrations. The addition of NAA along with BAP for multiple shoot proliferation proved to be detrimental as it encouraged undesirable root formation under multiple shoots.…”
Section: Discussionmentioning
confidence: 99%
“…But unlike the latter, the formulations with relatively lower concentrations resulted in poorly developed multiple shoots, which were pale green and lanky in appearance. This may be due to the minimum levels of exogenous PGRs required to balance with endogenous plant hormones for retaining the plant health (Alderete et al 2006), which was not present in the formulations with relatively lower concentrations. The addition of NAA along with BAP for multiple shoot proliferation proved to be detrimental as it encouraged undesirable root formation under multiple shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal segments (length: 0.5 cm) of four different plants ( Bacopa monnieri, Eupatorium triplinerve, Excoecaria agallocha , and Avicennia marina ) were disinfected by sonicating in water for 20 min and dipping in 70% ethanol for 1 min, followed by 25 min of sodium hypochlorite (25%)/Tween 80 (0.01%) solution and rinsed three times with distilled and sterile water [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Findings by Zuraida et al [17] showed that sub-culture of microshoots in a medium with 1 mg/L BAP produced the highest proliferation of pineapple plantlets. Furthermore, Alderete et al [18] reported that the nodal segments of Mecardonia tenella cultured in a medium with 1 mg/L BAP showed the best multiplication rates, with values around 29 shoots per explant. The positive effect of BAP and NAA in promoting the proliferation of shoots was also detected by Boulay [19], who indicated that the best shoot proliferation of Sequoia sempervirens occurred on MS medium with 0.5 -1.0 mg/L BAP and 0.02 mg/L NAA.…”
Section: Figure 1 Micropropagation Of Vanilla Planifolia On Ms Mediumentioning
confidence: 99%